SYMBOLIC ASPECTS OF A SECONDARY NEWS: А CASE STUDY ON MEDIA REPORTING ON APPEARANCE OF A PANTHER ON BORDERS OF REPUBLIC OF SERBIA - Lazarević Radak, Sanja (Political Review, 2024)
In November 2022 the media in Serbia reported that the black panther roams the forests of North Bačka. Based on John Langer's concept of "other news" and Kelsey's understanding of discursive mythologies, three media discourses on the appearance of the panther in Apatin were critically analyzed: 1. The panther as a metaphor of hostile otherness; 2. Panther as an imaginary friend and ally of ecological and other opposition; 3. Folklore on Panther as a narrative space of escape and a source of psychological comfort. The rich mythological potential of the panther, his power of transformation, hiding, disappearing, and reappearing enables the inclusion of discourses on various ambivalent meanings, among which hostile otherness and friendly affection and adoration stand out. In public discourse, the symbolic potential of Vojvodina gains importance as a place of wilderness and porous classification, as well as a space where seemingly incompatible otherness coexists. Placing these and another close phenomenon near the borders is related to the ambivalent nature of the panther. It is based on the representation of the border as an undefined space where fantastic encounters and mysterious otherness occur. The administrative alternation of the space where the panther appears and the proximity of the two administrative borders, Hungary and Croatia, will play a decisive role in enabling the panther to function as an internal, or in a radical form, hidden, dangerous, hostile otherness. In an apparently critical tone, the media reports that the news on the panther has ideologically divided the country into those who favor euthanasia and those whose concern for the panther's fate goes beyond ordinary existential concern. Understood as a part of an endangered world, marginal and wandering, displaced and exposed to risks caused by an inefficient state apparatus, the panther functions as a metaphor for the threat to Serbia's environment by the authorities as a source of ecological negligence. The panther, as a ferocious beast and as a good savage, cannot be deprived of its appeal, even when interest in its media potential wanes. As the protagonist of a newspaper story, he enables identification with heroes and saviors and further identification of the subject with his ordeals, sufferings, or triumphs. In this way, its use in the media is a universal tool for satisfying the fantasies of news consumers.
Keywords: panther; media; discourse; otherness; inner/external enemy